2023
DOI: 10.1136/flgastro-2022-102307
|View full text |Cite
|
Sign up to set email alerts
|

UK national trainee survey of hepatology training, research and the future workforce

Abstract: ObjectiveThe increasing prevalence of liver disease in the UK means there is a pressing need to expand the hepatology workforce. This survey aims to evaluate current hepatology training provision, and trainee attitudes towards future careers in hepatology.MethodAn electronic survey was distributed to higher specialty gastroenterology and hepatology trainees in the UK between March and May 2022.Results138 trainees completed the survey covering all training grades and regions of the UK. 73.7% reported receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Finally, increasing Consultant Gastroenterologist/Hepatologist numbers at non-specialist centres remains a challenge. Nearly half of UK Consultant Gastroenterologist/Hepatologist advertised posts remained unfilled in 2020, and a recent survey demonstrated that less than one-third of Hepatology trainees would want to be a Consultant in a non-specialist centre 24 25. Innovative job planning, including roles split across specialist and non-specialist centres particularly in areas of deprivation, may address this.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, increasing Consultant Gastroenterologist/Hepatologist numbers at non-specialist centres remains a challenge. Nearly half of UK Consultant Gastroenterologist/Hepatologist advertised posts remained unfilled in 2020, and a recent survey demonstrated that less than one-third of Hepatology trainees would want to be a Consultant in a non-specialist centre 24 25. Innovative job planning, including roles split across specialist and non-specialist centres particularly in areas of deprivation, may address this.…”
Section: Discussionmentioning
confidence: 99%